Nonadministration of thromboprophylaxis in hospitalized patients with HIV: A missed opportunity for prevention?. Issue 4 (24th January 2014) - Newman, Matthew J.; Kraus, Peggy S.; Shermock, Kenneth M.; Lau, Brandyn D.; Haut, Elliott R.; Hobson, Deborah B.; Streiff, Michael B.
<x xml:space="preserve">Abstract</x> BACKGROUND Hospitalized patients with human immunodeficiency virus (HIV) appear to be at increased risk of venous thromboembolism. Previous work at our institution has demonstrated that the proportion of doses administered varies between patients and locations. OBJECTIVE To compare the proportion of doses of thromboprophylaxis not administered between patients with and without HIV. DESIGN Using retrospective data, the proportion of nonadministered doses was determined in all hospitalized adults and stratified by HIV status. SETTING Large, urban, academic medical center in Baltimore, Maryland. PATIENTS Data were available for 4947 patient visits, 583 of which were by patients with HIV. Most visits by patients with HIV were to a designated HIV care unit. MEASUREMENTS Proportion of doses of thromboprophylaxis not administered, and documented reasons for dose nonadministration. RESULTS A total of 42, 870 doses were prescribed. The proportion of doses not administered was greater for patients with HIV (23.5%) compared with patients without HIV (16.1%, odds ratio [OR]: 1.59, 95% confidence interval [CI]: 1.49‐1.70, P < 0.001). Documented dose refusal accounted for a greater proportion of nonadministered doses in patients with HIV (15.9% vs 10.8%, OR: 1.56, 95% CI: 1.43‐1.70, P < 0.0001). On the HIV care unit, the proportion of doses not administered was greater for patients with HIV (26.4% vs 13.1%, OR: 2.39, 95% CI: 1.93‐2.96, P < 0.001). Within this unit, documented dose refusal was greater for patients with HIV (13.7% vs 10.7%, OR: 1.32, 95% CI: 1.16‐1.51, P < 0.0001). CONCLUSIONS Nonadministration and documented refusal of thromboprophylaxis appear to be more common in patients with HIV at our institution. Journal of Hospital Medicine 2014;9:215–220. © 2014 Society of Hospital Medicine